Medium in Singular - Průchová, Andrea (Teorie vědy / Theory of Science, 2013)
review: W. J. T. MITCHELL - Mark B. N. HANSEN (eds.), Critical Terms for Media Studies. Chicago - London: University of Chicago Press 2010, 353 s.